A method for producing composite polyaluminium chloride ferric salt

By adding modified palygorskite and modifiers to polyaluminum ferric chloride, a composite polyaluminum ferric chloride salt with enhanced flocculation, adsorption and antibacterial properties is formed, which solves the problem of removing phosphorus and microbial pollutants in the existing technology. Solve the problem of deficiencies and achieve more efficient water treatment results.

CN118954745BActive Publication Date: 2025-01-24HENGYANG JIANHENG IND DEV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411443235.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-16
Publication Date
2025-01-24
Estimated Expiration
2044-10-16

AI Technical Summary

Technical Problem

The existing polymeric aluminum chloride has poor adsorption performance on phosphorus elements when treating wastewater and lacks antibacterial properties, making it difficult to completely remove phosphorus and microbial contaminants in wastewater.

Method used

By adding modified slopes to polymer aluminum chloride iron to form a composite of slope-polymer-polymer aluminum chloride, it improves its flocculation and adsorption performance, and the introduction of antibacterial performance through the introduction of the modified agent.

Benefits of technology

It significantly improves the flocculation, adsorption performance, and antibacterial performance of composite poly -chloride and iron salt, so that it can efficiently remove a variety of pollutants in sewage, including phosphorus and microorganisms.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a production method of a composite polyaluminium chloride iron salt, and belongs to the technical field of composite materials. The following raw materials are included in parts by weight: 100-120 parts of deionized water, 20-30 parts of polyaluminium chloride iron, and 10-20 parts of modified palygorskite. The prepared composite polyaluminium chloride iron salt, by adding palygorskite, palygorskite has a large specific surface area and abundant nanopores, which can improve the adsorption and flocculation of the composite polyaluminium chloride iron salt; and can form a palygorskite-polyaluminium chloride iron colloidal composite with polyaluminium chloride iron, further improving the flocculation ability; by modifying palygorskite, compared with ordinary palygorskite, the flocculation ability is stronger, and it also has significant antibacterial properties, and the performance is stable; therefore, the composite polyaluminium chloride iron salt prepared by the present invention has stable and efficient adsorption performance, flocculation performance and antibacterial performance, and has important application value in the field of water treatment technology.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of composite materials, and in particular relates to a production method of composite polyaluminium chloride ferric salt. Background Art

[0002] Water purification technology is fast becoming an essential aspect of modern life as conventional water resources become increasingly scarce, the quality of drinking water deteriorates over time due to various activities such as the development of manufacturing and agriculture, water pollution caused by additives and toxic heavy metals, and increased water use depletes and causes salt water pollution.

[0003] Polyaluminium ferric chloride is referred to as PAFC, and its general chemical formula is [Al2(OH) n Cl 6-n ] m ·[Fe 2( OH) n Cl 6-n ] m (1≤n≤5, m≤10) is a new type of inorganic polymer flocculant. It has both the excellent flocculation performance and strong charge neutralization ability of polyaluminium chloride and the adsorption performance of polyferric chloride. It combines the excellent performances of both polyaluminium and polyferric chloride, and overcomes the disadvantages of high residual aluminium concentration in water after polyaluminium chloride treatment and poor stability of polyferric chloride. It is widely used in the field of water treatment because of its fast reaction speed, large floccules, fast sedimentation and strong filterability when treating wastewater, especially in decolorization, removal of COD and turbidity.

[0004] The composition of pollutants in sewage is very complex. Polyaluminum ferric chloride can effectively remove heavy metal ions in sewage, but its adsorption performance for phosphorus in phosphorus sewage is poor and it is difficult to completely remove it. In addition, polyaluminum ferric chloride does not have antibacterial properties and is difficult to remove bacteria, viruses, and cysts in water. Therefore, it is urgent to invent a composite polyaluminum ferric chloride with good phosphorus removal effect and antibacterial properties to meet the higher demands in the field of water treatment. Summary of the invention

[0005] The purpose of the present invention is to overcome the defects of the prior art and provide a method for producing composite polyaluminium chloride ferric salt.

[0006] The purpose of the present invention can be achieved through the following technical solutions:

[0007] A method for producing composite polyaluminium chloride ferric salt comprises the following steps:

[0008] After mixing polyaluminum ferric chloride and modified palygorskite in deionized water, the mixture was placed on a constant temperature magnetic stirrer, heated and stirred at 80° C. for 6 h, and ultrasonically treated for 1 h, and then allowed to stand for solid-liquid separation, the upper deionized water was removed, and the remaining solid was dried at 105° C., ground, and passed through a 100-mesh sieve to obtain a composite polyaluminum ferric chloride.

[0009] Furthermore, the raw materials are calculated in parts by weight as follows: 100-120 parts of deionized water, 20-30 parts of polyaluminium ferric chloride, and 10-20 parts of modified palygorskite.

[0010] Palygorskite has a unique rod crystal structure. It can be quickly hydrated under high-speed stirring conditions. Due to the van der Waals force and electrostatic attraction between the rod crystals, it is easy to form a stable network structure. Polyaluminum ferric chloride contains multiple binding sites such as -OH, which can combine with palygorskite to form a palygorskite-polyaluminum ferric chloride colloidal composite material, thereby improving the flocculation ability of the composite polyaluminum ferric chloride salt. In addition, the modified palygorskite that mainly plays an adsorption role in the molecular structure of polyaluminum ferric chloride and the hydroxyaluminum ions that mainly play an electrical neutralization and bridging role coordinate and complement each other, thereby enhancing its flocculation performance.

[0011] Further, the modified palygorskite is prepared by the following steps:

[0012] A1. Place palygorskite and distilled water in a flask and shake vigorously to obtain a palygorskite dispersion. Add γ-aminopropyltriethoxysilane (KH-550) to the palygorskite dispersion and oscillate in a constant temperature oscillator at 25°C for 24 hours. Filter, dry, crush, and pass through a 200-mesh sieve to obtain pre-modified palygorskite.

[0013] A2. Add N,N-dimethylformamide (DMF), dicyclohexylcarbodiimide (DCC, dehydrating agent) and pre-modified palygorskite into a flask. After uniform dispersion by ultrasonic treatment for 45 minutes, add the modifier, slowly heat up to 55°C, start magnetic stirring (speed 1200r / min), stop heating after stirring for 4 hours, wait until the temperature in the reaction bottle drops to 25°C, filter, wash with anhydrous ethanol 3-4 times, and freeze-dry to obtain modified palygorskite.

[0014] Furthermore, in step A1, the ratio of palygorskite, distilled water and γ-aminopropyltriethoxysilane is 1-10 g:80-100 g:2-5 g.

[0015] Furthermore, in step A2, the ratio of the amount of N,N-dimethylformamide, dicyclohexylcarbodiimide, pre-modified palygorskite, and modifier is 80-100 mL: 10-20 g: 5-10 g: 10-15 g.

[0016] Palygorskite is a natural hydrated magnesium-aluminum silicate clay mineral with a layered chain structure and nanorod-like crystal morphology. It has the characteristics of large specific surface area, abundant nanopores and active surface groups, and thus exhibits excellent adsorption, catalytic and ion exchange properties. By grafting modifiers, the modifiers are not easy to migrate and fall off, making their performance long-lasting and stable.

[0017] Furthermore, the modifier is prepared by the following steps:

[0018] S1. Stearic acid, dicyclohexylcarbodiimide, diethylenetriamine and xylene were mixed in a three-necked flask equipped with a stirring reflux device, stirred vigorously at room temperature, and the temperature was raised to 150°C. After reflux reaction for 2 hours, a water separator was connected and the temperature was continued to be raised to 200°C until no water was generated. After the reaction was completed, the mixture was filtered and distilled under reduced pressure to obtain intermediate 1; the ratio of stearic acid, dicyclohexylcarbodiimide, diethylenetriamine and xylene was 28.5g:20.6g:11.3g:100mL;

[0019] Stearic acid first undergoes an amidation reaction with diethylenetriamine, and then a cyclization reaction occurs after the temperature is raised. By controlling the molar ratio of stearic acid to diethylenetriamine to be close to 1:1 and a slight excess of diethylenetriamine, only one amino group on diethylenetriamine participates in the reaction to obtain intermediate 1. The specific reaction process is as follows:

[0020] ;

[0021] S2. In a three-necked flask equipped with a stirring device, 5-chloro-2-methylisothiazoline-3-one, sodium hydroxide, triethylamine and toluene were added in sequence, and the mixture was stirred at room temperature for 30 minutes, and then 5-hydroxyisophthalic acid was added. The reaction temperature was controlled to 65°C, and the reaction was kept warm for 6 hours. After the reaction was completed, the filtrate was filtered, and the filtrate was washed 3 times with saturated brine, dried over anhydrous magnesium sulfate, and filtered again. Column chromatography was used for purification (the eluent was a mixed solvent of benzene / ethyl acetate in a volume ratio of 3:1), and the eluent was removed by rotary evaporation to obtain intermediate 2; the ratio of the amount of 5-chloro-2-methylisothiazoline-3-one, sodium hydroxide, triethylamine, toluene and 5-hydroxyisophthalic acid was 14.8g:3.9g:15mL:100mL:18.2g;

[0022] Sodium hydroxide reacts with the hydroxyl group on 5-hydroxyisophthalic acid to form sodium phenolate with stronger nucleophilicity. Sodium phenolate, as a nucleophilic reagent, attacks the carbon atom connected to the chlorine atom on 5-chloro-2-methylisothiazoline-3-one, so that the chlorine atom is replaced, thereby forming an ether bond; triethylamine removes the hydrogen chloride generated by the reaction to obtain intermediate 2; the specific reaction process is as follows:

[0023] ;

[0024] S3. In a three-necked flask equipped with a stirring device, the intermediate 1, intermediate 2, dicyclohexylcarbodiimide and toluene were mixed and stirred evenly, and reacted for 4 hours under a 55°C water bath condition. After the reaction was completed, the mixture was filtered and the solvent was removed by distillation under reduced pressure to obtain intermediate 3; the ratio of intermediate 1, intermediate 2, dicyclohexylcarbodiimide and toluene was 35.1 g:30.2 g:20.6 g:150 mL;

[0025] The amino group on intermediate 1 and the carboxyl group on intermediate 2 undergo an amidation reaction. Under the action of a dehydrating agent, the reaction can be carried out under relatively mild conditions. By controlling the molar ratio of intermediate 1 to intermediate 2 to be close to 1:1 and a slight excess of intermediate 2, only one carboxyl group on intermediate 2 participates in the reaction, thereby obtaining intermediate 3. The specific reaction process is as follows:

[0026] ;

[0027] S4. In a three-necked flask equipped with a stirring device, the intermediate 3, methyl iodide and toluene were mixed and stirred uniformly, the reaction temperature was controlled at 85°C, the reaction was carried out for 8 hours, and after the reaction was completed, the modifier was obtained by distillation under reduced pressure; the ratio of the intermediate 2, methyl iodide and toluene was 62.8g:28.2g:150mL;

[0028] The tertiary amino group on the intermediate 3 undergoes an alkylation reaction with methyl iodide to obtain a modifier (quaternary ammonium product); the structure of the modifier is shown below:

[0029] ;

[0030] The prepared modifier molecule contains imidazoline, isothiazolinone, quaternary ammonium salt and long carbon chain structure, among which imidazoline can improve the flocculation effect of composite polyaluminium chloride ferric salt; the introduced isothiazolinone has excellent properties such as strong antibacterial ability, environmental safety and broad antibacterial spectrum, and forms a disulfide bond with the sulfhydryl group on cysteine ​​in the pathogen protein through the bond active site on the heterocyclic ring, thereby inactivating the protein to achieve the purpose of sterilization, and giving the composite polyaluminium chloride ferric salt significant antibacterial performance; in addition, the introduction of quaternary ammonium salt as an excellent antibacterial structure further enhances the antibacterial performance of the composite polyaluminium chloride ferric salt, and the quaternary ammonium salt as a cation can also adsorb anionic pollutants, thereby improving the adsorption performance of the composite polyaluminium chloride ferric salt on pollutants; finally, the introduction of long carbon chain can be interspersed in the molecular chain of polyaluminium chloride ferric, thereby ensuring the stability of the performance of the modifier.

[0031] Beneficial effects of the present invention:

[0032] 1. The composite polyaluminum ferric chloride prepared by the present invention can improve the adsorption and flocculation properties of the composite polyaluminum ferric chloride by adding palygorskite, which has a large specific surface area and abundant nanopores; and can form a palygorskite-polyaluminum ferric chloride colloidal composite material with polyaluminum ferric chloride, further improving the flocculation ability;

[0033] 2. By modifying palygorskite, compared with ordinary palygorskite, it has stronger flocculation ability, significant antibacterial properties, and stable performance;

[0034] Therefore, the composite polyaluminium chloride ferric salt prepared by the present invention has stable and efficient adsorption performance, flocculation performance and antibacterial performance, and has important application value in the field of water treatment technology. DETAILED DESCRIPTION

[0035] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0036] Example 1

[0037] Preparation of modifier:

[0038] S1. In a three-necked flask equipped with a stirring reflux device, 28.5 g of stearic acid, 20.6 g of dicyclohexylcarbodiimide, 11.3 g of diethylenetriamine and 100 mL of xylene were mixed, vigorously stirred at room temperature, and the temperature was raised to 150° C. After reflux reaction for 2 h, a water separator was connected, and the temperature was continued to be raised to 200° C. until no water was generated and the reaction was completed, filtered, and distilled under reduced pressure to obtain intermediate 1;

[0039] S2. In a three-necked flask equipped with a stirring device, 14.8 g of 5-chloro-2-methylisothiazoline-3-one, 3.9 g of sodium hydroxide, 15 mL of triethylamine and 100 mL of toluene were added in sequence, and the mixture was stirred at room temperature for 30 min. Then, 18.2 g of 5-hydroxyisophthalic acid was added, and the reaction temperature was controlled to 65 ° C. The reaction was kept warm for 6 h. After the reaction was completed, the mixture was filtered, and the filtrate was washed 3 times with saturated brine, dried over anhydrous magnesium sulfate, filtered again, and purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 3:1), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0040] S3, in a three-necked flask equipped with a stirring device, 35.1 g of intermediate 1, 30.2 g of intermediate 2, 20.6 g of dicyclohexylcarbodiimide and 150 mL of toluene were mixed and stirred evenly, and reacted for 4 h under a 55° C. water bath condition. After the reaction was completed, the mixture was filtered and the solvent was removed by distillation under reduced pressure to obtain intermediate 3;

[0041] S4. In a three-necked flask equipped with a stirring device, 62.8 g of intermediate 3, 28.2 g of methyl iodide and 150 mL of toluene were mixed and stirred evenly. The reaction temperature was controlled at 85° C. and the reaction was carried out for 8 h. After the reaction was completed, vacuum distillation was performed to obtain a modifier.

[0042] Example 2

[0043] Preparation of modifier:

[0044] S1. In a three-necked flask equipped with a stirring reflux device, 57.0 g of stearic acid, 41.2 g of dicyclohexylcarbodiimide, 22.6 g of diethylenetriamine and 200 mL of xylene were mixed, vigorously stirred at room temperature, and the temperature was raised to 150° C. After reflux reaction for 2 h, a water separator was connected, and the temperature was continued to be raised to 200° C. until no water was generated and the reaction was completed, filtered, and distilled under reduced pressure to obtain intermediate 1;

[0045] S2. In a three-necked flask equipped with a stirring device, 29.6 g of 5-chloro-2-methylisothiazoline-3-one, 7.8 g of sodium hydroxide, 30 mL of triethylamine and 200 mL of toluene were added in sequence, and the mixture was stirred at room temperature for 30 min. Then, 36.4 g of 5-hydroxyisophthalic acid was added, and the reaction temperature was controlled to 65 ° C. The reaction was kept warm for 6 h. After the reaction was completed, the mixture was filtered, and the filtrate was washed 3 times with saturated brine, dried over anhydrous magnesium sulfate, filtered again, and purified by column chromatography (the eluent was a mixed solvent of benzene / ethyl acetate, and the volume ratio of the two was 3:1), and the eluent was removed by rotary evaporation to obtain intermediate 2;

[0046] S3, in a three-necked flask equipped with a stirring device, 70.2 g of intermediate 1, 60.4 g of intermediate 2, 41.2 g of dicyclohexylcarbodiimide and 300 mL of toluene were mixed and stirred evenly, and reacted for 4 h in a 55° C. water bath. After the reaction was completed, the mixture was filtered and the solvent was removed by distillation under reduced pressure to obtain intermediate 3;

[0047] S4. In a three-necked flask equipped with a stirring device, 125.6 g of intermediate 3, 56.4 g of methyl iodide and 300 mL of toluene were mixed and stirred evenly. The reaction temperature was controlled at 85° C. and the reaction was carried out for 8 h. After the reaction was completed, the modified agent was obtained by distillation under reduced pressure.

[0048] Example 3

[0049] Preparation of modified palygorskite:

[0050] A1. 1 g of palygorskite and 80 g of distilled water were placed in a flask and shaken vigorously to obtain a palygorskite dispersion. 2 g of γ-aminopropyltriethoxysilane was added to the palygorskite dispersion and the mixture was shaken in a constant temperature oscillator at 25 ° C for 24 h. The mixture was filtered, dried, crushed, and passed through a 200 mesh sieve to obtain pre-modified palygorskite.

[0051] A2. Add 80 mL of N,N-dimethylformamide, 10 g of dicyclohexylcarbodiimide and 5 g of pre-modified palygorskite into a flask, disperse evenly by ultrasonication for 45 min, add 10 g of the modifier prepared in Example 1, slowly heat to 55 ° C, turn on magnetic stirring (speed 1200 r / min), stop heating after stirring for 4 h, filter after the temperature in the reaction bottle drops to 25 ° C, wash 3 times with anhydrous ethanol, and freeze-dry to obtain modified palygorskite.

[0052] Example 4

[0053] Preparation of modified palygorskite:

[0054] A1. 10 g of palygorskite and 100 g of distilled water were placed in a flask and shaken vigorously to obtain a palygorskite dispersion. 5 g of γ-aminopropyltriethoxysilane was added to the palygorskite dispersion and the mixture was shaken in a constant temperature oscillator at 25 ° C for 24 h. The mixture was filtered, dried, crushed, and passed through a 200 mesh sieve to obtain pre-modified palygorskite.

[0055] A2. Add 100 mL of N,N-dimethylformamide, 20 g of dicyclohexylcarbodiimide and 10 g of pre-modified palygorskite into a flask, disperse evenly by ultrasonication for 45 min, add 15 g of the modifier prepared in Example 2, slowly heat to 55 ° C, turn on magnetic stirring (speed 1200 r / min), stop heating after stirring for 4 h, filter after the temperature in the reaction bottle drops to 25 ° C, wash 4 times with anhydrous ethanol, and freeze-dry to obtain modified palygorskite.

[0056] Example 5

[0057] 20 g of polyaluminium ferric chloride (purchased from Wuhan Fengyao Tonghui Chemical Products Co., Ltd., with a basicity of 79.5%, a main chemical composition of Al2O311.24%, and elemental iron 3.2%) and 10 g of the modified palygorskite obtained in Example 3 were mixed in 100 g of deionized water, placed on a constant temperature magnetic stirrer, heated and stirred at 80° C. for 6 h, ultrasonically treated for 1 h, and then allowed to stand for solid-liquid separation, the upper deionized water was removed, and the remaining solid was dried at 105° C., ground, and sieved through a 100-mesh sieve to obtain a composite polyaluminium ferric chloride.

[0058] Example 6

[0059] 25 g of polyaluminium ferric chloride (purchased from Wuhan Fengyao Tonghui Chemical Products Co., Ltd., with a basicity of 79.5%, and its main chemical composition of Al2O311.24%, elemental iron 3.2%) and 15 g of modified palygorskite obtained in Example 4 were mixed in 110 g of deionized water, placed on a constant temperature magnetic stirrer, heated and stirred at 80°C for 6 h, ultrasonically treated for 1 h, and then allowed to stand for solid-liquid separation, the upper deionized water was removed, and the remaining solid was dried at 105°C, ground, and passed through a 100-mesh sieve to obtain a composite polyaluminium ferric chloride.

[0060] Example 7

[0061] 30 g of polyaluminium ferric chloride (purchased from Wuhan Fengyao Tonghui Chemical Products Co., Ltd., with a basicity of 79.5%, and its main chemical composition of Al2O311.24%, elemental iron 3.2%) and 20 g of the modified palygorskite obtained in Example 4 were mixed in 120 g of deionized water, placed on a constant temperature magnetic stirrer, heated and stirred at 80 ° C for 6 h, ultrasonically treated for 1 h, and then allowed to stand for solid-liquid separation, the upper deionized water was removed, and the remaining solid was dried at 105 ° C, ground, and passed through a 100 mesh sieve to obtain a composite polyaluminium ferric chloride.

[0062] Comparative Example 1

[0063] Ordinary palygorskite of the same mass was used to replace the modified palygorskite in Example 7, and the remaining steps were the same as in Example 7.

[0064] Comparative Example 2

[0065] Commercially available polyaluminium ferric chloride produced by Henan Aierfuke Chemical Co., Ltd. was used.

[0066] The following performance tests were performed on Examples 5-7 and Comparative Examples 1-2:

[0067] Determine the removal rate of the sample for arsenic (concentration 0.1 mg / L) and lead (concentration 0.1 mg / L) in sewage;

[0068] Determine the removal rate of phosphorus in phosphorus-containing wastewater by the sample;

[0069] Determine the removal rate of COD and BOD in sewage by the sample;

[0070] The bactericidal effect was tested by using the "Static Sterilization Test of Heterotrophic Bacteria" in the "Analysis and Test Methods for Cooling Water" compiled by the Production Department and Development Department of China Petrochemical Corporation;

[0071] The measured results are shown in Table 1:

[0072] Table 1

[0073] ;

[0074] It can be seen from the above table that the composite polyaluminum ferric chloride prepared in the embodiment of the present invention has a high removal rate for various pollutants and excellent antibacterial properties, and has important application value in the field of water treatment technology.

[0075] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0076] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. A method for producing a composite polyaluminium chloride ferric salt, characterized in that: The following steps are involved: After mixing polyaluminium ferric chloride and modified palygorskite in deionized water, heating and stirring at 80°C for 6 hours, ultrasonically treating for 1 hour, standing, drying, grinding, and sieving to obtain composite polyaluminium ferric chloride; Wherein, the modified palygorskite is prepared by the following steps: A1. Place palygorskite and distilled water in a flask, shake vigorously to obtain a palygorskite dispersion, add γ-aminopropyltriethoxysilane to the palygorskite dispersion, shake at 25° C. for 24 h, filter, dry, crush, and sieve to obtain pre-modified palygorskite; A2. Add N,N-dimethylformamide, dicyclohexylcarbodiimide and pre-modified palygorskite into a flask, perform ultrasonication for 45 min, add a modifier, raise the temperature to 55 °C and stir for 4 h, after the temperature in the reaction flask drops to 25 °C, filter, wash and dry to obtain modified palygorskite; Wherein, the modifier is prepared by the following steps: S1. Stearic acid, dicyclohexylcarbodiimide, diethylenetriamine and xylene are mixed, vigorously stirred at room temperature, refluxed at 150°C for 2h, connected to a water separator, and the temperature is continued to rise to 200°C until no water is generated and the reaction is completed. The mixture is filtered and distilled under reduced pressure to obtain intermediate 1. The molar ratio of stearic acid to diethylenetriamine is controlled to be close to 1:1 and the diethylenetriamine is slightly excessive so that only one amino group on the diethylenetriamine participates in the reaction. S2, 5-chloro-2-methylisothiazoline-3-one, sodium hydroxide, triethylamine and toluene were mixed in sequence, stirred for 30 minutes, 5-hydroxyisophthalic acid was added, and the mixture was reacted at 65°C for 6 hours. After the reaction was completed, the mixture was filtered, washed, dried, filtered again, purified by column chromatography, and rotary evaporated to obtain intermediate 2; S3, mixing intermediate 1, intermediate 2, dicyclohexylcarbodiimide and toluene, stirring evenly, reacting at 55° C. for 4 hours, filtering and distilling under reduced pressure to obtain intermediate 3; controlling the molar ratio of intermediate 1 to intermediate 2 to be close to 1:1 and intermediate 2 to be slightly excessive, so that only one carboxyl group on intermediate 2 participates in the reaction; S4. The intermediate 3, methyl iodide and toluene are mixed and stirred evenly, and reacted at 85° C. for 8 h. After the reaction is completed, the mixture is distilled under reduced pressure to obtain a modifier.

2. The method for producing a composite polyaluminium chloride ferric salt according to claim 1, characterized in that: In step S1, the ratio of stearic acid, dicyclohexylcarbodiimide, diethylenetriamine and xylene is 28.5 g:20.6 g:11.3 g:100 mL.

3. The method for producing a composite polyaluminium chloride ferric salt according to claim 1, characterized in that: In step S2, the ratio of the amount of 5-chloro-2-methylisothiazoline-3-one, sodium hydroxide, triethylamine, toluene, and 5-hydroxyisophthalic acid is 14.8 g: 3.9 g: 15 mL: 100 mL: 18.2 g.

4. The method for producing a composite polyaluminium chloride ferric salt according to claim 1, characterized in that: In step S3, the ratio of the amount of intermediate 1, intermediate 2, dicyclohexylcarbodiimide and toluene is 35.1 g:30.2 g:20.6 g:150 mL.

5. The method for producing a composite polyaluminium chloride ferric salt according to claim 1, characterized in that: In step S4, the ratio of the amount of intermediate 2, methyl iodide and toluene is 62.8 g:28.2 g:150 mL.

6. The method for producing a composite polyaluminium chloride ferric salt according to claim 1, characterized in that: The raw materials of the composite polyaluminium ferric chloride salt are as follows in parts by weight: 100-120 parts of deionized water, 20-30 parts of polyaluminium ferric chloride, and 10-20 parts of modified palygorskite.

7. The method for producing a composite polyaluminium chloride ferric salt according to claim 1, characterized in that: In step A1, the ratio of palygorskite, distilled water and γ-aminopropyltriethoxysilane is 1-10 g:80-100 g:2-5 g.

8. The method for producing a composite polyaluminium chloride ferric salt according to claim 1, characterized in that: In step A2, the ratio of the amount of N,N-dimethylformamide, dicyclohexylcarbodiimide, pre-modified palygorskite and modifier is 80-100 mL: 10-20 g: 5-10 g: 10-15 g.

Citation Information

Patent Citations

  • Preparation method of illite smectite mixed clay mycotoxin adsorbent

    CN103846078A

  • Preparation method of starch adhesive

    CN108864985A